Author Correction: Universality of defect-skyrmion interaction profiles - Imara Lima Fernandes (Nature Portfolio, 2019)
The original version of this Article contained an error in the Acknowledgements, which incorrectly omitted from the end the following: ‘We acknowledge the computing time granted by the JARA-HPC Vergabegremium and VSR commission on the supercomputer JURECA at Forschungszentrum Jülich.’ This has been corrected in both the PDF and HTML versions of the Article.